The Effect of Diamond Fraud on Academic Fraud Behavior - Siti Salwawati; Muhamad Nur Afif; Yoyok Priyo Hutomo (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The study aims to address the impact of Pressure, Opportunity, Rationalization, and Capability on academic cheating behavior with academic integrity as moderated variables on scholarship students at Economic and Business Faculty, Djuanda University. The study was a descriptive quantitative study that used primary data with a number of 106 students obtained with saturated sampling techniques. The data analysis techniques performed in this study are either MRA or moderated regression analysis made using SPSS. Studies have concluded that Pressure, Rationalization, and Capability have an impact on academic cheating behavior, while Opportunity has no effect on academic cheating behavior. Furthermore, Rationalizing also has an effect on academic cheating behavior with academic integrity as moderate variables, while Pressure, Opportunity, and Capability have no effect on academic cheating behavior with academic integrity as a moderation variable.